Cervical Sympathetic Block Prolongs the Latency and Reduces the Amplitude of Trigeminal Somatosensory Evoked Potentials on the Contralateral Side. Issue 1 (February 2015) - Kawaguchi, Jun; Matsuura, Nobuyuki; Kasahara, Masataka; Ichinohe, Tatsuya
Abstract : Purpose: The purpose of this study was to investigate the latency and amplitude of trigeminal somatosensory evoked potentials to clarify how nerve function on the contralateral side is affected after cervical sympathetic block (CSB). Methods: Subjects comprised 16 volunteers. For CSB, the tip of a needle was contacted with the transverse process of the sixth cervical vertebra on the right side, and lidocaine was injected. Trigeminal somatosensory evoked potentials were recorded bilaterally from C5/C6 scalp positions. Pupil diameters were also measured. Electrical stimulations were applied to the left-side lower lip, and trigeminal somatosensory evoked potentials waveforms derived from both sides of the scalp were recorded. Then, electrical stimulations were applied to the right-side of the lower lip, and recording was again performed. Recordings were performed at 5, 15, and 30 minutes after CSB. Results: On the CSB side, pupil diameter decreased at 5 and 15 minutes after CSB. Trigeminal somatosensory evoked potentials at contralateral stimulation showed a prolongation of the latency in both P20 and N25 components on bilateral recording sites 5 and 15 minutes after CSB. Trigeminal somatosensory evoked potentials' amplitude at contralateral stimulation was smaller than at ipsilateral stimulation 5 minutes after CSB. Conclusions: Cervical sympathetic block prolongs the latency and reduces the amplitude of trigeminal somatosensory evoked potentials on the contralateral side.